2018
DOI: 10.1007/s40520-018-1100-0
|View full text |Cite
|
Sign up to set email alerts
|

Midlife predictors of active and healthy aging (AHA) among older businessmen

Abstract: Background Active and healthy aging (AHA) is an important phenomenon in aging societies. Aims Our aim was to investigate midlife predictors of AHA in a socioeconomically homogenous male cohort. Methods In 2010, AHA was defined in the Helsinki Businessmen Study (men born in 1919–1934) with six criteria: (1) being alive, (2) responding to the mailed survey, (3) no reported cognitive problems, (4) feeling of happiness, (5) no difficulties in act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Our findings agree with most previous studies which have shown the importance of lifestyle factors on HA [2,[5][6][7]9]. In prior longitudinal observational studies, a positive association between physical activity and HA has consistently been shown [5][6][7], independently of the definition and variable operationalization. In a study in five Latin American countries [2], physically active participants were most likely to be successful agers at follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings agree with most previous studies which have shown the importance of lifestyle factors on HA [2,[5][6][7]9]. In prior longitudinal observational studies, a positive association between physical activity and HA has consistently been shown [5][6][7], independently of the definition and variable operationalization. In a study in five Latin American countries [2], physically active participants were most likely to be successful agers at follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, in the HR analysis, overweight and obesity increased the risk of losing HA, and no relationship was found with HA77 and HA90. This result might be explained because higher BMI in midlife has been associated with unhealthy survival [6], which in our study would lead to loss of the HA status in midlife. Therefore, many prevalent cases, which lost HA status in midlife, were excluded from the analysis and this relationship might be understated.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results also support this theory. Prevention and advanced treatment of chronic diseases enable an individual to maintain functionality and age "successfully" [23][24][25][26][27][28][29][30][31][32]. Cardiovascular risk factors are well known, and their treatments have developed during past decades [33], although intensity of treatment varies between various risk factors despite effective treatments for, e.g., hypertension and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition of the modifiable physiological and psychosocial risk factors that impact our lifespans is important, as it enables early interventions [ 10 , 11 ], and therefore research conducted at mid-life is especially significant. Among the well-established risk factors determining longevity recognized to date are smoking habits [ 12 , 13 ], diabetes mellitus [ 14 ], obesity [ 14 ], cardiovascular health [ 15 ], and sedentary lifestyle [ 15 ].…”
Section: Introductionmentioning
confidence: 99%